INTRODUCING WHO SPECIAL PROGRAM FOR RESEARCH AND TRAINING IN TROPICAL DISEASES - A. Nadim (Tehran University of Medical Sciences, 1977)
After giving a brief account about the history of the special program, the objectives and scope of the special program have been discussed and the Iranian scientists and institutes for research and training in the field of public health are invited to cooperate with this special program of the World Health Organization for better control of prevalent tropical disease in the country. Out of the six diseases that at the present time are of interest to the special program, four of them are important public health problems in Iran, namely malaria, schistosomiasis, leishmaniasis and leprosy.